Calpain-2 protein influences chikungunya virus replication and regulates vimentin rearrangement caused by chikungunya virus infection - Li, Jia; Zheng, Kang; Shen, Huilong; Wu, Hua; Wan, Chengsong; Zhang, Renli; Liu, Zhimin (Frontiers in Microbiology, 2023)
Chikungunya fever (CHIF), a vector-borne disease transmitted mainly by Aedes albopictus and Aedes aegypti, is caused by Chikungunya virus (CHIKV) infection. To date, it is estimated that 39% of the world's population is at risk of infection for living in countries and regions where CHIKV is endemic. However, at present, the cellular receptors of CHIKV remains not clear, and there are no specific drugs and vaccines for CHIF. Here, we used calpain-2 protein activity inhibitor III and specific siRNA to effectively suppress the replication of CHIKV. Western blot was used to determine the level of the calpain-2 protein and vimentin. Immunofluorescence was also operated for detecting the rearrangement of vimentin caused by CHIKV infection. Our results indicated that inhibiting the expression or activity of calpain-2 protein may suppress CHIKV replication and repress the intracellular vimentin rearrangement caused by CHIKV infection, which could be important for understanding the biological significance of CHIKV replication and the future development of antiviral strategies.